Silver and copper nanoparticles stabilized on ionic liquids-functionalized polyhedral oligomeric silsesquioxane (POSS): Highly active and recyclable hybrid catalysts. (1st October 2019) - Akbari, Ali; Naderahmadian, Aylar; Eftekhari-Sis, Bagher
Graphical abstract: New supporting material based on POSS-ionic liquid was synthesized. Ag and Cu metal nanoparticles were immobilized on POSS-ionic liquid. Catalytic performances of the as prepared hybrid materials were investigated in click reaction and 4-NP reduction. Abstract: Two novel heterogeneous hybrid catalysts were successfully synthesized using octa-aminopropyl polyhedral oligomeric silsesquioxane hydrochloride salt (OA-POSS) and ionic liquids, followed by immobilization of Cu and Ag nanoparticles. The obtained hybrid catalysts, Cu@POSS-ILs and Ag@POSS-ILs, were characterized using FT-IR, SEM, EDX, TEM, XRD and TGA. Catalytic studies demonstrated that Cu@POSS-ILs was an excellent catalyst for click reaction in aqueous medium. Furthermore, Ag@POSS-ILs was also exhibited to be an active catalyst for 4-nitrophenol (4-NP) reduction. Simple preparation and easy catalysts recovery and recyclability of Cu@POSS-ILs and Ag@POSS-ILs for at least 3 and 6 runs, respectively, without loss of catalytic activity could be considered as important advantageous from catalytic application point of view.